The Role of Foreign Networks for Firm Export of Services - Andreas Hatzigeorgiou; Magnus Lodefalk (Örebro University School of Business, 2015)
This study formalizes the idea that that the world can become 'smaller' through firms' strategic trade-related decisions. We investigate whether firm investment in obtaining access to foreign networks impacts exports of services by estimating a fixed effects panel model on a comprehensive firm-level dataset for Sweden. In particular, we examine investment in links through the hiring of immigrants. Because trade barriers are higher for services than for goods, and because trade in services is more sensitive to informal trade barriers, firm investment in access to foreign networks could especially help to increase services exports. However, investment in foreign links could benefit overall access within the same cluster of firms, which reduces the incentive for an individual firm to invest in such linkages itself. The novel results suggest a positive and significant influence of firm investment in foreign networks – through the hiring of foreign-born workers – on both the propensity to export services as well as the intensity of exports. Instrumental variable estimation mitigates endogeneity concerns. Weaker export experience enhances the role of investment in foreign networks in terms of the propensity to export. The skill level of foreignborn workers and the time that has elapsed since immigration also impact the degree to which firms can utilize investment in foreign-born personnel to gain access to networks abroad. Our findings provide a new understanding of how firms can overcome trade barriers that specifically impede services by investing in foreign networks, such as through hiring foreign-born personnel, and emphasize the role of foreign-born population to promote services exports.
Keywords: D80; F10; F22; J61; L14; 330; networks; firms; trade; services; immigration